Green Supply Chain Management (GSCM): A Research Agenda - Alina Shamsuddin; Eta Wahab; Wan Nurul Karimah Wan Ahmad; Nor Hazana Abdullah; Mohd Syaiful Abdul Hamid (International Journal of Supply Chain Management, 2020)
The concept of green supply chain management (GSCM) is now gaining more attention among practitioners due to its ability to help companies address environmental issues. Nevertheless, studies on GSCM practices and outcomes extensively come from multinational companies compared to fully owned Malaysian companies, especially the Small Medium Enterprises (SMEs). This conceptual paper discusses GSCM in global context and explores further directions of GSCM research in Malaysia. The discussions led to conclusions that the main drivers of GSCM implementation are mainly the pressure of regulators, customers and public awareness. Moreover, the implementation can have positive impacts on organizations economic performance and preservation of the environment. Consequently, more research is needed on the implementation of GSCM among Malaysian SMEs, especially in terms of the key practices from the perspectives of the practitioners